Composition, characterization and performance studies of hybrid rocket motor doped with metallic additives and high entropy alloy - Mohamad Jamil, Nur Arifah; Abd Razak, Najihah; Ismail, Izham Izzat; Nordin, Norhuda Hidayah; Azami, Muhammad Hanafi (The Aeronautical and Astronautical Society of the Republic of China, 2024)
The poor combustion efficiency and low regression rate of the Hybrid Rocket Motor (HRM) limit its use in propulsion systems. Therefore, a thorough examination of the use of high-energy additives such as metals and alloys were carried out to improve the performance of the Hybrid Rocket Motor (HRM) in terms of regression rate. A lab-scale motor was developed to conduct experimental studies by incorporating boron, aluminum, and FeCoNiAlBSi High Entropy Alloy (HEA) into the Paraffin wax as a regression rate enhancer. Different compositions of additives were prepared to obtain the optimal performance of the hybrid rocket. Characterizations of the solid fuel were carried out by X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) to determine the crystal structure and morphology of the solid fuel with the energetic additives. From the static firing test, the sample fuel doped with 5 wt% of boron had the highest regression rate, followed by 7 wt% of aluminum and 5 wt% of high entropy alloy, with regression rates of 1.45, 1.37, and 1.20, respectively. Regression rate analysis reveals that High Entropy Alloy may improve the hybrid rocket's performance.